Views of instructors towards students learning english public speaking at a malaysian university - Ahmad Taufik Hidayah, Abdullah; Mohd Nazri, Latiff Azmi (2019)
Public speaking was one of the most feared situations faced by many people, including public speaking in the English language. Speaking English in front of the public was really a daunting task for many people, including students of universities. This study addressed issues related to English public speaking at the university from the views of instructors who taught the English public speaking course. Some topics discussed were the common weaknesses of university students in delivering English public speaking, the causes of the weaknesses and some recommendations for students to improve their English public speaking. This was a qualitative research design where eleven instructors teaching English public speaking were interviewed and the gathered data were analyzed using thematic analysis and presented using Atlas. ti version 7. One of the theories employed in the study was the Uncertainty Reduction Theory that made their anxiety level increase. The study revealed that some common weaknesses of students were lack of confidence, limited vocabulary and grammar. Some contributing causes of the weaknesses were lack of reading, lack of ideas, and lack of self-esteem. Some recommendations were then forwarded to solve the problems such as giving the motivation to the students to speak, read and think in the English language and make a lot of practices.